The sustainable management design of oxbow lake to determine the factors in lake management in Buluh Cina village, Indonesia. Issue 4 (4th June 2020) - Susilo, Adi
Abstract : Purpose: The purpose of this study at the level of sustainability of oxbow lake was intended to determine the status of sustainability, leverage attributes and driving factors in the management of oxbow lake in Buluh Cina village in Kampar, Riau, Indonesia. Design/methodology/approach: The types of data collected include primary data and secondary data. Data was collected using survey methods, library research, laboratory analysis and interviews. The analytical method used this study is multidimensional scaling (MDS) analysis and prospect analysis. Sustainability analysis is done using the MDS analysis approach with the help of RapOxbow software and compared to Monte Carlo analysis results. Findings: The current sustainability status of the management of Lake Baru ecosystem according to a number of dimensions is considered sustainable with a sustainability index value of 50.95. Meanwhile, the analysis results of each dimension shows that the sustainability index for the ecological dimension is 42.56 and the sustainability index for the economic dimension is 47.44, which means that the index is less sustainable. Originality/value: The approach of this research is MDS analysis and prospect analysis and research locations in Buluh Cina village in Kampar, Indonesia which have never been studied before. This is one of few studies that investigates comprehensively the analysis of management sustainability, especially in the dimensions of ecology, economics and socio-culture, especially in Indonesia.